Cervical Cancer Patient Experiences with Chemotherapy in Conducting Their Role as Wives - Jamila Rambe; Siti Saidah Nasution; Muara Panusunan Lubis (Indonesian Journal of Global Health Research, 2024)
Wives who suffer from cervical cancers and receive chemotherapy treatment potentially have the potential to experience a decrease in the reproductive function of the organs so that the role as a wife experiences changes such as impaired gynecological functions which result in nonfulfillment of sexual desires, pain during intercourse, bleeding, emotional disturbances, and fatigue so that the daily activities of cervical cancer sufferers experience a significant decrease. Objective to understand cervical cancer patients' experiences with chemotherapy in conducting their role as wives. the study was a qualitative design with a phenomenological approach. Data were collected using an interview with 8 participants and analyzed using colaizzi. Then, it is transcribed and analyzed repeatedly. The second step, analyzing, is conducted by extracting significant statements, categorizing, and understanding the essential meaning. In the third step, describing, the researcher communicates, concludes, and defines the phenomenon. 6 Themes are found in this research: 1) conducting the role as a wife part, 2) sexual relationship disorders, 3) self –concept disorder 4) anxiety of cancer 5) medication side effects, 6) getting the family support. The study result indicates that despite the side effects of chemotherapy experienced by wives who suffer from cervical cancer, they still can conduct their role as wives supported by the family.